2019
DOI: 10.1155/2019/3545939
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Analysis of Flexible Shaft and Elastic Disk Rotor System Based on the Effect of Alford Force

Abstract: Taken the flexible shaft and elastic disk rotor system as the research object, vibration differential equations are established by the modal synthesis method. Based on the Runge–Kutta method of direct integration, dynamic equations are solved successfully. Then, the effects of Alford force caused by the airflow excitation are researched on the stability and dynamic response. The results show modal vibration of the disk takes a great effect on the coupled natural frequency of shaft transverse vibration in the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In recent years, there are an increasing number of scholars who pay attention to the nonlinear vibration of the seal-bearingrotor system because of its strong nonlinear characteristics, including oil-film instability and other coupling faults, such as the airflow-induced vibration [21][22][23][24][25][26][27][28][29][30][31][32]. For example, Wang et al [21] studied the effect of the real high-pressure methane gas properties on the nonlinear behavior of the seal-rotor system.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there are an increasing number of scholars who pay attention to the nonlinear vibration of the seal-bearingrotor system because of its strong nonlinear characteristics, including oil-film instability and other coupling faults, such as the airflow-induced vibration [21][22][23][24][25][26][27][28][29][30][31][32]. For example, Wang et al [21] studied the effect of the real high-pressure methane gas properties on the nonlinear behavior of the seal-rotor system.…”
Section: Introductionmentioning
confidence: 99%
“…Using uniformly distributed load of 5 N, tensile stresses and deflections were obtained for all cases. Many types of stresses and deflections in all directions for this shaft are obtained and discussed as following: In figures (3,4,5,6) when the eccentricity (e = 0.1x10 -3 ) the value of Von Mises stress (σ von ) begins from (33) Mpa at (N= 1000 R.P.M) and reach to (36.5) Mpa at (N= 4400 R.P.M) but (under the same conditions) in the case of the eccentricity (e = 0.3x10 -3 ) will be (43) Mpa at (N= 1000 R.P.M) and reach to (161) Mpa at (N= 4400 R.P.M). In figures (7,8,9,01), when the eccentricity (e = 0.1x10 -3 ) the value of (σ 3 ) stress begin from (-39.4) Mpa at (N= 1000 R.P.M) and reach to (-41.7) Pa at (N= 4400 R.P.M) but (under the same conditions) in the case the eccentricity (e = 0.3x10 -3 ) will be (-51.1) Mpa at (N= 1000 R.P.M) and reach to (-203) Mpa at (N= 4400 R.P.M).…”
Section: Resultsmentioning
confidence: 99%
“…deflection was take place at the midpoint of the shaft while the stresses and deflection are concentrating at the bottom of the bearing due to concentrating forces on this area. Wenjun Yang et al [4] investigate the vibration differential equation of a shaft -disc rotor system by the model synthesis method. Runge-Kutta "s direct integration method has been used to extract the equation of system.…”
Section: ][2]mentioning
confidence: 99%
“…Taking the flexible shaft and elastic disk rotor system as the research object, Yang et al established the vibration differential equation with the modal synthesis method and solved the equation by using the Runge−Kutta method. The results showed that the increase of speed and disk radius will lead to the increase of rotor response, which can help to improve the stability of the system by adjusting the support position [6]. Li et al analyzed the impact of nonlinear coupling factor and blade-bending vibration to dynamic characteristics of rotor-bearing system and the results indicated that the Alford force caused by blade tip clearance makes the motion state of the system more complex [7].…”
Section: Introductionmentioning
confidence: 99%
“…will lead to the increase of rotor response, which can help to improve the stability of the system by adjusting the support position [6].Li et al analyzed the impact of nonlinear coupling factor and bladebending vibration to dynamic characteristics of rotorbearing system and the results indicated that the Alford force caused by blade tip clearance makes the motion state of the system more complex [7].…”
Section: Introductionmentioning
confidence: 99%